(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The paper presents a paper as an empirical study of self-help group towards women empowerment participation in local community development of Kamrup district in Assam. The study aimed at assessing conflict management strategies adopted by women empowerment through self-help group constitutes an emerging and fast-growing trend towards social and economic development of the nation. A survey method was adopted for conducting the paper, by the investigator especially for this purpose. The study was primarily qualitative in nature; a historical and analytical methodology was adopted while preparing the study. The sample of the study was conducted in Garoimari sub-division in Kamrup district of Assam. Therefore, the present work is aimed at studying the changing narrative of identity construction among Self Help Group (SHG) is one of the innovative and much needed concepts to accelerate the women entrepreneurship, women self-employment and women empowerment. The present study was conducted to explore the impact of women Self Help Group on women empowerment through income generation, increased communication skill, decision making ability and awareness and enhanced social status. The purpose of the present study is to impact for achieving quality, quantity, equality of opportunity with respect to nature of human rights. Hence, achieving balanced participation of women in political, public decision-making and also achieving gender mainstreaming in all policies and measures. However, gender equality in politics is not merely achieving an equal share of seats and positions. The major micro-enterprise the women SHG members associated with is related to agriculture. The major problem of the women SHG members in the study area is improper training facility. Thus study the suitable recommendations for enhancing the plan and its remedies.